A three-tiered mentorship approach for supporting high school students interested in science, technology, engineering, and mathematics (STEM) careers - Brittney D. Browning; Janiece S. Glover; Lindsay R. Meredith; Anna E. Kirkland; Kathryn S. Gex; Rachel L. Tomko; Felicity Duong; Lindsay M. Squeglia (Journal of Clinical and Translational Science)
Racially and ethnically minoritized individuals, first-generation college students, and women are significantly underrepresented in science, technology, engineering, and mathematics (STEM) careers. This lack of equal representation limits creativity and progress in these fields and perpetuates systemic barriers that discourage students from pursuing STEM pathways. This special communication introduces the three-tiered mentorship model employed in the Teen Science Ambassador Program (TSAP), which incorporates senior mentors, near-peer mentors, and high school ambassadors (i.e., mentees) to promote education, hands-on research, and career development in STEM for underrepresented students. We discuss the benefits and challenges of the three-tiered model and offer recommendations for optimizing its effectiveness to enhance mentorship experiences for all participants. Findings from the TSAP program suggest that the three-tiered approach benefited all participants: high school ambassadors gained STEM skills and confidence, near-peer mentors developed leadership and communication abilities, and senior mentors improved mentorship skills. However, the effectiveness of near-peer mentorship is highly dependent on clearly defined roles and structured involvement. Thus, feedback collected from each mentorship tier was used to inform subsequent iterations of the program. The layered mentorship structure fostered a sense of community and belonging, which is crucial for retaining individuals from underrepresented groups in STEM.